English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

The solution to the equation 2(n - 3) + 3 = 3(4 - n) + 10

a. n = 4

b. n = 5

c. n = 3

d. n = 7

e. none of the above

2007-05-30 10:16:18 · 7 answers · asked by pretty woman 1 in Science & Mathematics Mathematics

7 answers

b

Explanation:
2(n - 3) + 3 = 3(4 - n) + 10
2n - 6 + 3 = 12 - 3n + 10
2n - 3 = 22 - 3n
2n + 3n = 22 + 3
5n = 25
n = 25/5 = 5

2007-05-30 10:19:11 · answer #1 · answered by psbhowmick 6 · 1 1

B) N=5

2007-05-30 10:26:50 · answer #2 · answered by JustMe 2 · 0 1

Solve the "n" variable... 2(n - 3) + 3 = 3(4 - n) + 10

First: eliminate parenthesis - use the Distribution Method.

2(n)+2(- 3)+3 = 3(4)+3(- n)+10
2n+(-6)+3 = 12+(-3n)+10
2n-6+3 = 12-3n+10
2n - 3 = 22 - 3n

Sec: combine "like" terms - add 3 with both sides (when you move a term to the opposite side, always use the opposite sign).

2n - 3+3 = 22 - 3n+3
2n = 22+3-3n
2n = 25-3n

*Add "3n" with both sides.

2n+3n = 25-3n+3n
2n+3n = 25
5n = 25

Third: isolate "n" on one side (left) - divide both sides by 5.

5n/5 = 25/5
n = 25/5
n = 5

2007-05-30 11:53:23 · answer #3 · answered by ♪♥Annie♥♪ 6 · 0 0

if you open out the equation you get

2n -6 +3 = 12 -3n +10 which simplifies to

2n -3 = 22 -3n if you put the "n" to one side you get

5n = 25 divide both sides by 5


n = 5

2007-05-30 10:22:10 · answer #4 · answered by MattG83 1 · 0 0

2n-6+3=12-3n+10
2n-3=-3n+22
-2n -2n
-3=-5n+22
-22 -22
-25=-5n
n= 5

2007-05-30 10:26:16 · answer #5 · answered by hey_thanks_you_guys 3 · 0 0

2(n-3)+3=3(4-n)+10
2n-6+3=12-3n+10
2n-3=22-3n
2n+3n-3=22-3n+3n
5n-3=22
5n-3+3=22+3
5n=25
n=5 b.

2007-05-30 10:24:37 · answer #6 · answered by Dave aka Spider Monkey 7 · 0 0

2n-6+3=12-3n +10
5n=25
n=5, answer b

2007-05-30 10:21:22 · answer #7 · answered by WraitH 3 · 0 0

fedest.com, questions and answers